APPLICATION OF MODERN INFORMATION TECHNOLOGIES OF LEARNING IN CONDITIONS OF TRANSFORMATION OF MODERN SOCIETY - Tugalov Ismatjon Hatamovich (Journals Park Publishing, 2022)
The article discusses the role and importance of the scientific and technical equipment of the educational process in order to obtain a quality competitive education. Only a comprehensive, connected by a single didactic concept, the use of an organizational and planning system will increase the effectiveness of computer training in the system of professional training of specialists.
Keywords: professional training of personnel, traditional and non-traditional (innovative) forms, methods and means of training.